2008
DOI: 10.1103/physrevlett.101.177402
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Matrix Softening of Ge-As-Se Network Glasses

Abstract: Sub-band-gap irradiation of a series of bulk Ge-As-Se glass samples with a tunable laser source shows that photostructural processes in chalcogenide glasses are strongly dependent on the covalent network connectivity. The photoexcitation process is affected by the bond density as well as the network rigidity. Photostructural changes such as photodarkening and photoexpansion decrease and tend to vanish in overcoordinated glass in accordance with the rigidity percolation threshold. Also, the intensity required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 41 publications
10
51
0
Order By: Relevance
“…The importance of Se atoms in holographic grating formation is clearly indicated by the compositional dependence of the efficiency of the process, manifesting in a remarkably decreasing reaction of the material to light illumination with increasing Ge content [40]. The results obtained clearly indicate that the modulation depth of the created holographic gratings under light irradiation in Ge-Se thin films decreases with addition of Ge.…”
Section: Raman Spectroscopic Investigationssupporting
confidence: 53%
“…The importance of Se atoms in holographic grating formation is clearly indicated by the compositional dependence of the efficiency of the process, manifesting in a remarkably decreasing reaction of the material to light illumination with increasing Ge content [40]. The results obtained clearly indicate that the modulation depth of the created holographic gratings under light irradiation in Ge-Se thin films decreases with addition of Ge.…”
Section: Raman Spectroscopic Investigationssupporting
confidence: 53%
“…It has previously been shown that the efficiency of photostructural changes greatly depend on the mean coordination of the glass network. 46 The extent of photodarkening in the Ge-As-Se system has been plotted in Fig. 11 as a function of ͗r͘ along with the values of n obtained in this study for ͗r͘ = 2.2, 2.4, and 2.5 in the Ge-Se system.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies 46 have described the effect of mean coordination ͑͗r͒͘ of the glass network on photoinduced behaviors. The mean coordination number of Ge x Se 1−x are given in Table I.…”
Section: Mean Coordination Effectmentioning
confidence: 99%
“…Their formation and effect over the Ge-Se bonding makes the systems more sensitive towards light illumination. The decreased amount of chalcogen atoms in the Ge rich sample reduces the mass effect of these electrons, and combined with the rigidity of the material reduces the range of the illumination induced effects [31]. The results on photo-induced volume change and the additional possibility of mass transport in Ge-Se system under the gradient intensity of illumination show a potential of these materials for surface relief recording, as it was investigated and presented for As-Se and As-S layer structures [32,33].…”
Section: Discussionmentioning
confidence: 99%